Perfil de dietas vs uso de aditivos em animais confinados - Pavoni, Andrielle Abreu de Oliveira (2022)
When evaluating the mode of action of the additives, we see that the association of additives can be advantageous, not only in dense diets, in helping to control ruminal pH, but also in less dense diets, with a focus on increasing fermentative efficiency. Therefore, the objective of the present study was to evaluate the effect of the association of an ionophore additive (monensin sodium) with nonionophore additives (zinc bacitracin or virginiamycin) on the performance of feedlot beef cattle receiving less dense diets. The study was carried out at the Agroceres Multimix Research Center, located in Patrocínio-MG. A total of 144 non-castrated Nellore steers were used, with an average age of 30 months and initial average live weight of 399 kg (±22.6 kg), distributed in a randomized block design, which were submitted to 4 treatments with 6 repetitions each, totaling 6 animals per experimental unit. The treatments were: diet with roughage to concentrate ratio (V:C) of 15:85 plus 25 mg/kg DM of monensin (15:85M); diet with 70:30 V:C supplemented with 25 mg/kg MS monensin (30:70M); diet with 30:70 V:C supplemented with 25 mg/kg DM of monensin and 7 mg/kg DM of zinc bacitracin (30:70MB); diet with 30:70 V:C added with 25 mg/kg DM of monensin and 25 mg/kg DM of virginiamycin (30:70MV). The animals were confined for 114 days, with the initial 18 days for the adaptation of the animals to the experimental diets. Animals fed diets containing a higher proportion of roughage (30:70) had higher (p<0.10) daily dry matter intake than those fed a diet containing a higher proportion of concentrate (15:85). The 30:70M and 307:0MV diets provided higher average daily gain (p<0.05) than the 15:85M diet, but there was no difference in carcass gain between treatments, which resulted in a lack of significant difference between treatments for feed conversion and carcass conversion. The animals submitted to the 15:85M and 30:70MB treatments showed better gain and carcass yield than those fed the 30:70MV and 30:70M diets. The association of the additives monensin plus zinc bacitracin in diets with greater participation of roughage promoted better carcass gain when compared to the diet with greater participation of concentrate and without association.